2016
DOI: 10.1038/srep37820
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Profiling of Circulating Tumour Cells Identifies Notch1 as a Principal Regulator in Advanced Non-Small Cell Lung Cancer

Abstract: Knowledge on the molecular mechanisms underlying metastasis colonization in Non-Small Cell Lung Cancer (NSCLC) remains incomplete. A complete overview integrating driver mutations, primary tumour heterogeneity and overt metastasis lacks the dynamic contribution of disseminating metastatic cells due to the inaccessibility to the molecular profiling of Circulating Tumour Cells (CTCs). By combining immunoisolation and whole genome amplification, we performed a global gene expression analysis of EpCAM positive CTC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…NOTCH1 has emerged as a driver connecting active signaling pathways, providing a potential therapeutic target for lung cancer transmission. 41 Recent studies have demonstrated that the human NOTCH1 gene is involved in metastasis and cancer stem cell maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…NOTCH1 has emerged as a driver connecting active signaling pathways, providing a potential therapeutic target for lung cancer transmission. 41 Recent studies have demonstrated that the human NOTCH1 gene is involved in metastasis and cancer stem cell maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…With this panel we evaluated critical steps and characteristics considered highly relevant for prostate CTCs biology [ 19 , 20 ]. With this approach, previously validated in colorectal, endometrial and lung cancer [ 21 23 ], we identified a panel of biomarkers with demonstrated prognostic significance for progression free survival (PFS) and OS in mCRPC under taxane treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia or overexpression of HIF-1α induces the EMT via NF-κB in pancreatic cancer cells [70] and inhibition of NF-κB deregulates EMT [71] Promotes PCa cell survival, tumor invasion, metastasis, and chemoresistance [72,73] NSCLC-CTC gene expression profile was associated with cellular movement, cell adhesion and differentiation, and cell-tocell signaling linked to PI3K/AKT, ERK1/2, and NF-κβ pathways [74]. No report in PCa CTCs…”
Section: Nf-κbmentioning
confidence: 99%